PERNIKAHAN ADAT TICAK KACANG DAYAK SIANG : (Sebuah Analisis Sosial Masyarakat Desa Datah Koto Kecamatan Murung Kabupaten Murung Raya) - Wina Yunita (Prodi Sosiologi FISIP UPR, 2019)
The purpose of this study was to find out the process of Ticak Kacang traditional wedding ceremony. The method in this research is descriptive qualitative research method. Descriptive research is a research method that collects information about the research subject obtained by research through observation, interviews, and documentation. The results of this study that the traditional marriage of Ticak Kacang is a way for the community to maintain the sanctity of the village to avoid actions that are not in accordance with the prevailing customary norms and show the simple life that they apply in the village of Datah Koto. The procedure used where the bride and groom will prepare all the requirements or tools needed during the traditional wedding ceremony for Ticang Kacang. The bride and groom will be prayed with a position sitting on a Gong with the handsoft the two brides holding a Sawang leaf. And the social function of this customary marriage is to increase solidarity among fellow citizens.